Transmigration Program With Animal Ilushandry Model in Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT: Transmigration program with animal husbandry model is aimed to ensure efficiency of the land potential and natural food in order to raise animal production, truogh the companys or private investment and is directed to meet the requirements of national animal protein and to boost the non-oil export. It is planned that die transmigrants should become self-supporting animal piodncers who possess privately owned lands, house, laud for foodstuff and for animal food. Each trarismigrant family is given 2 Ha of land, consisting of 0.5 Ha of houselot, 0.51-la of arable land and I Ha of animal feeding land. The transmigration sites with animal husbiuldry model will be developed trough the cooperation of Public Undertaking (IIUMN) trough private entrepreneurs on a pattern of plasma-nucleus partnership. fhc role of the 'maces enterprise in this case is to grand credit for animal feeding input besides technical establishment and marketing. Up to the present, animal component in the transmigranc farming system is only considered as asupporting activity to the mind activities in the existing developed models Experiences in executing transmigration program show that animal component of the fanning system can significantly increase the transmigrant's income. In Sosa II transmigration site, North Sumatra, for example, transmigrant's income during the third year of settlement from animal component of the farming system reached more than one million nipiali per year.